From Kuching to Cardiff: Sport in Colonial Sarawak, 1945-63. Issue 7 (18th October 2021) - Bridges, Brian
Abstract: Formerly governed as a family fiefdom, Sarawak in South-east Asia had a brief existence after World War II as a British Crown Colony until it became a constituent part of the newly-created Malaysia in 1963. Using contemporaneous documentary and newspaper sources together with oral history interviews of athletes, the post-1945 development of sport within this new member of the formal British empire is examined. Particularly notable was the trend, with the active encouragement of the British colonial authorities, for Sarawakian athletes to carry the flag for their state in international sporting events starting from the 1958 Empire and Commonwealth Games in Wales. However, although sport has frequently served to enhance national identity in former colonies, in Sarawak these sporting activities, even on the international stage, played only a limited role in stimulating national consciousness.